Geohazard Mitigation Select Proceedings of VCDRR 2021 - Adhikari, Basanta Raj.; Kolathayar, Sreevalsa; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents the select proceedings of the Virtual Conference on Disaster Risk Reduction (VCDRR 2021). It emphasizes on the role of civil engineering for a disaster resilient society. It presents latest research in geohazards and their mitigation. Various topics covered in this book are land use, ground response, liquefaction, and disaster mitigation techniques. This book is a comprehensive volume on disaster risk reduction (DRR) and its management for a sustainable built environment. This book will be useful for the students, researchers, policy makers and professionals working in the area of civil engineering, especially disaster management. .
Geohazard investigation and management: An introduction -- Rheological Characteristics of Sand Stabilized with Colloidal Silica for Barrier Material and Liquefaction Mitigation -- A Study on Liquefaction Susceptibility Analysis of Earthen dams -- Evaluation of the effectiveness of flexible debris flow barriers for control of Huaycos using satellite images and GIS, in the basin of Rimac River, Peru -- Investigation of flow structures along the embankment generated nearby finite riparian vegetation -- Sediment Yield Estimation and Reservoir Sedimentation Assessment Using Geospatial Tools: A Case Study of Tehri Dam Reservoir.
Keywords: Environmental engineering; Civil engineering; Natural disasters; Geotechnical engineering; Environmental Civil Engineering; Natural Hazards; Geotechnical Engineering and Applied Earth Sciences; Civil engineering -- Congresses; Hazard mitigation -- Congresses